Improving Psychiatric Care for Older People Barbara Robb's Campaign 1965-1975 - Hilton, Claire (Mental Health in Historical Perspective,, 2017)
This book is open access under a CC BY 4.0 license. This book tells the story of Barbara Robb and her pressure group, Aid for the Elderly in Government Institutions (AEGIS). In 1965, Barbara visited 73-year-old Amy Gibbs in a dilapidated and overcrowded National Health Service psychiatric hospital back-ward. She was so appalled by the low standards that she set out to make improvements. Barbara's book Sans Everything: A case to answer was publicly discredited by a complacent and self-righteous Ministry of Health. However, inspired by her work, staff in other hospitals 'whistle-blew' about events they witnessed, which corroborated her allegations. Barbara influenced government policy, to improve psychiatric care and health service complaints procedures, and to establish a hospitals' inspectorate and ombudsman. The book will appeal to campaigners, health and social care staff and others working with older people, and those with an interest in policy development in England, the 1960s, women's history and the history of psychiatry and nursing.